Pengaruh Budaya Organisasi dan Kualitas Sumber Daya Manusia terhadap Kinerja Pegawai dengan Motivasi Sebagai Variabel Intervening pada Dinas Perindustrian dan Perdagangan Provinsi Jambi - Yusman, Heri; Syeikh, Saiyid; Yamali, Fakhrul Rozi (J-MAS (Jurnal Manajemen dan Sains), 2024)
The aim of this research is to describe organizational culture, employee quality, employee motivation and employee performance at the Department of Industry and Trade of Jambi Province. Then analyzed the influence of organizational culture and the quality of human resources on motivation, analyzed the influence of organizational culture and the quality of human resources on employee performance, analyzed the influence of motivation on employee performance, and analyzed the influence of organizational culture and human resources. . quality on employee performance is analyzed. The organizational culture is then analyzed. and the quality of human resources that encourage employees to excel. This research is research that uses descriptive and control research methods, namely methods for studying a group of people, an object, a situation and a state of mind. a system whose aim is to create a picture, a systematic picture according to the facts being investigated. The aim of control research is to test hypotheses regarding the influence between variables in this research. The analytical tool used in this research is path analysis and the sample is a counting method of 96 employees. Data were analyzed using SPSS.22. The research results show that the organizational culture is in good condition, the quality of personnel is in good condition, motivation is high and personnel performance is also high, as are organizational culture and personnel quality. resources have a positive and significant effect simultaneously or partially. motivation, organizational culture and quality of human resources simultaneously and partially have a positive and significant effect on an employee's performance and motivation has a positive and significant effect on the performance of employees at the Jambi Province Department of Industry and Trade.